The Role of Sharia Accountant for Sustainable Development Goals (SDGs) - Mauliyah, Nur Ika (Journal of Islamic Economics Perspectives, 2019)
Accountants have various activities that support every financial reporting activity. Developing Islamic accounting is now increasingly diverse activities the existence of Islamic accounting considered. The United Nations initiated sustainable development goals as SDGs. The SDGs are consensus or agreement from 193 member states of the United Nations (UN) and agreed on their achievements. SDGs has 17 goals and 169 achievement targets with a target of 15 years, namely from 2015-2030. SDGs and financial reports needed in carrying out the desired activities to get achieve the target. Islamic accounting is almost SDGs with sharia accounting with the same goal in advancing a better life. Indonesian Institute of Accountants by making provisions for Islamic accounting guidelines.